Trakai Castle Court Acts of 1660–1661: From the Collection of Vilnius University Library. V - Ušinskienė, Viktorija (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English]The catalogue was prepared within the framework of the research project “Court Books of the Grand Duchy of Lithuania (GDL): Digitization and Database” realized by Vilnius University Library in 201122014 (VUL, No. LIT–5–19). The paper deals with the previously unexplored Trakai Castle Court Acts of 1660–1661 (F7–MDGs, 1660–1661) from the VUL collection. It presents Part V of the critical catalogue of the manuscripts written in Polish and Old Byelorussian (Ruthenian) languages, also providing short descriptions of documents Nos. 775–822 (pp. 827–877). These documents are important for the research of Lithuanian, Polish and Byelorussian history. Information accumulated in them reflects a broad political, social and cultural panorama of the multilingual GDL society. It enables us to consider them as unique reference books that represent the changing sociolinguistic situation of the GDL.
Keywords: Court Books of the Grand Duchy of Lithuania, manuscript collections, Trakai Castle Court Acts, digital collections of Vilnius University Library